Enzymatic Logic of Ubiquitin Chain Assembly - Deol, Kirandeep K.; Lorenz, Sonja; Strieter, Eric R. (Frontiers in Physiology, 2019)
Protein ubiquitination impacts virtually every biochemical pathway in eukaryotic cells. The fate of a ubiquitinated protein is largely dictated by the type of ubiquitin modification with which it is decorated, including a large variety of polymeric chains. As a result, there have been intense efforts over the last two decades to dissect the molecular details underlying the synthesis of ubiquitin chains by ubiquitin-conjugating (E2) enzymes and ubiquitin ligases (E3s). In this review, we highlight these advances. We discuss the evidence in support of the alternative models of transferring one ubiquitin at a time to a growing substrate-linked chain (sequential addition model) versus transferring a pre-assembled ubiquitin chain (en bloc model) to a substrate. Against this backdrop, we outline emerging principles of chain assembly: multisite interactions, distinct mechanisms of chain initiation and elongation, optimal positioning of ubiquitin molecules that are ultimately conjugated to each other, and substrate-assisted catalysis. Understanding the enzymatic logic of ubiquitin chain assembly has important biomedical implications, as the misregulation of many E2s and E3s and associated perturbations in ubiquitin chain formation contribute to human disease. The resurgent interest in bifunctional small molecules targeting pathogenic proteins to specific E3s for polyubiquitination and subsequent degradation provides an additional incentive to define the mechanisms responsible for efficient and specific chain synthesis and harness them for therapeutic benefit.